Design of a Web-Based Management Application for Jamu Bu Tri Shop with Sales Analysis Features - Daru Caraka; Heny Pratiwi; Vilianty Rafida (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Digital transformation that comes from information technology has been the main game changer for businesses of all sectors. Even the least expected ones, like micro, small and medium enterprises that are MSMEs like herbal medicine shops in Indonesia, have been impacted. Jamu Bu Tri Shop is using a manual management system which leads to problems such as inaccurate data recording, lack of real-time product tracking, slow transaction processes, and difficult financial reporting. This study is about a web-based store management application with sales analysis features through the use of the Rapid Application Development methodology. Observation, interview of the owner and employees of the shop and documentation were the data collection methods. The system design was done through the Unified Modeling Language diagrams like Use Case Diagrams, Activity Diagrams, and Class Diagrams. This application can automate product management, sales transactions, category and supplier management, expense recording, and integrated report generation. The main novelty is an analytical dashboard that provides the interaction of data visualization through the line chart, bar graph, and donut chart. Black Box testing checked all system functions with 100% accuracy in eight main modules and the System Usability Scale evaluation gave a score of 91.67 with Grade A. The implementation results showed that there were considerable improvements in the operation: transaction recording time was reduced by 90%, monthly report preparation was enhanced by 98%, product stock checking was improved by 94%, and best-selling product identification was sped up by 99.7%.